HYPEROSTOSIS IN MURAENESOX TALABONOIDES (BLEEKER) - Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
Hyperossification has been observed in supra-occipital bones, some of the dorsal fin rays and vertebrae of eel Mnraenesox talabonoides (Bleeker), in all the specimens above 82 cm.